OPTIMALISASI PRODUKTIVITAS KERJA MELALUI PENINGKATAN PELATIHAN DAN PENGEMBANGAN PEGAWAI - Itto Turyandi Turyandi (KarismaPro, 2021)
The problem statement in this research is work productivity at PT. Pragata Makmur Persada, based on initial observations, is suspected to be caused by the lack of optimal employee training and development programs, so the researchers conducted research using quantitative methods, with a correlation approach and testing the effect of data analysis using descriptive analysis and path analysis. The results showed that employee training was included in the very good category with an average dimension score of 184. Employee development was included in the very good category with an average dimension score of 189. Employee productivity at PT. Pragata Makmur Persada is included in the very good category with an average score of 189. Research also proves that work productivity is influenced by an increase in employee training and development by 80.2%. Partially the increase in training affects the work productivity of employees by 32.75%. And employee development affects work productivity at PT. Pragata Makmur Persada by 47.46%. The conclusion shows that increased training affects employee work productivity quite significantly, and employee development affects work productivity very significantly at PT. Pragata Makmur Persada. Kata Kunci:  Pelatihan, Pengembangan dan Produktivitas Kinerja